Atomic level characterization in corrosion studies. (28th July 2017) - Marcus, Philippe; Maurice, Vincent
Abstract : Atomic level characterization brings fundamental insight into the mechanisms of self-protection against corrosion of metals and alloys by oxide passive films and into how localized corrosion is initiated on passivated metal surfaces. This is illustrated in this overview with selected data obtained at the subnanometre, i.e. atomic or molecular, scale and also at the nanometre scale on single-crystal copper, nickel, chromium and stainless steel surfaces passivated in well-controlled conditions and analysed in situ and/or ex situ by scanning tunnelling microscopy/spectroscopy and atomic force microscopy. A selected example of corrosion modelling by ab initio density functional theory is also presented. The discussed aspects include the surface reconstruction induced by hydroxide adsorption and formation of two-dimensional (hydr)oxide precursors, the atomic structure, orientation and surface hydroxylation of three-dimensional ultrathin oxide passive films, the effect of grain boundaries in polycrystalline passive films acting as preferential sites of passivity breakdown, the differences in local electronic properties measured at grain boundaries of passive films and the role of step edges at the exposed surface of oxide grains on the dissolution of the passive film. This article is part of the themed issue 'The challenges of hydrogen and metals'.